Mechanisms of Thrombosis in Paraproteinemias: The Effects of Immunomodulatory Drugs - Zangari, Maurizio; Berno, Tamara; Zhan, Fenghuang; Tricot, Guido; Fink, Louis (Seminars in Thrombosis and Hemostasis, 2012)
The introduction of immunomodulatory drugs (IMiDs) has improved clinical outcome in patients with multiple myeloma (MM). However, their use has been associated with a higher risk of cardiovascular complications. The use of IMiDs with dexamethasone, chemotherapy, or in combination with erythropoietic agents enhances the risk of venous thromboembolism (VTE) up to 25%. The pathogenesis of this increased risk of VTE seen with IMiD-based combination therapy is not yet fully understood, but several mechanisms have been proposed to explain the development of this hypercoagulable state. In cancer patients, prothrombotic factors include age, chemotherapy, immobility, enhanced expression of tissue factor of malignant cells, circulating microparticles, and increased vascular endothelial growth factor (VEGF). In patients with paraproteinemias, immunoglobulin-specific mechanisms may also be involved and include hypofibrinolysis, hyperviscosity, procoagulant autoantibody production, effects of inflammatory cytokines, and acquired activated protein C resistance (APCR). In this review we will focus on IMiD-associated effects on specific thrombotic mechanisms.
Keywords: immunomodulatory drugs; paraproteinemias; venous thrombosis